Study on Sulfide Layer Attenuation Behavior of Smithsonite During Sulfidization Flotation - Zeng, Yong; Liu, Jian; Dong, Wenchao; Hao, Jiamei; Wang, Yu (Frontiers in Materials, 2020)
The S content on the surface of smithsonite plays a decisive role in smithsonite flotation. In this study, the attenuation behavior of smithsonite surface sulfide layer was investigated by inductive coupling plasma mass-spectrometric (ICP-MS) and X-ray photoelectron spectroscopic (XPS). The results of smithsonite surface S adsorption capacity tests indicated that smithsonite surface sulfide layer is not stable, and the S adsorption capacity decreased from 22.12 × 10−7 to 20.52 × 10−7 mol/g from 6 to 8 min with a decrease of 7.2%. NH4Cl can enhance the stability of S adsorption on the smithsonite surface. After adding NH4Cl, the S adsorption capacity on smithsonite surface for sulfidization 8 min was increased by 10.9%. However, the S falling off capacity tests showed that the S-species will fall off from smithsonite surface under mechanical stirring. The largest amount of falling off capacity is 3.701 × 10−7 mol/g, with a decreased percentage of 16.7%. XPS analysis indicated that monosulfide, disulfide, polysulph, sulphite, and sulfate are all the sources of the S-species falling off from the surface, and the relative content of disulfide on smithsonite surface has the greatest decreasing, reaching 0.33%. Mechanical stirring is an important reason for sulfide layer attenuation of smithsonite surface. Monosulfide, disulfide, and polysulph on smithsonite surface can be converted into soluble sulphite and soluble sulfate, resulting in the decrease of S content on smithsonite surface.